Functional differences between healthy and stressed soils: Rare and abundant root exudates as a regulatory switch for quorum sensing in rhizosphere microbiota - Yueyi Liu; Zhenchao Wu; Zeming Ye; Liangyang Mao; Xiujun Tu; Yuhao Guo; Weige Yao; Ying Yang; Shuo Li; Jie Kang; Baiyan Cai; Jingping Ge (Plant and Soil, 2026)

Study on the pro-inflammatory mechanism mediated by the RANK-SPP1 axis in macrophage immunomodulation during atherosclerosis - Qiyu Sun; Yanbo Hu; Zeming Sun; Mingyan Shang; Zhengyi Li; Juan Shen; Zhenzhen Cui; Jiaxin Yang; Xiaowen Ma; Min Li (Molecular and Cellular Biochemistry, 2026)

Enhanced long-term oxidative remediation of calcium sulfate encapsulated KMnO4 for phenol-contaminated soil - Jia Shen; Yaxian Hu; Zeming Xie; Zili Jiang; Doaa M. Mustafa; Yang Liu; Yue Han; Xiuxiu Ruan (Journal of Hazardous Materials, 2026)

Cohydrothermal carbonization of cellulose and organic matter from municipal sewage sludge for the controllable synthesis of N-doped porous carbon for supercapacitor electrodes - Linxin Yin; Chang Liu; Yulu Yang; Zihan Du; Guanzhong Mu; Zeming Zhao; Changqing Cao; Pei-Gao Duan; Krzysztof Kapusta (Journal of Environmental Management, 2026)

17β-estradiol-induced growth–defense tradeoffs in pak choi (Brassica) and implications for intake risk - Yang Chen; Junyue Wang; Zikang Zhang; Zeming Wang; Youai Zhang; Yanzheng Gao; Chao Qin; Wanting Ling (Journal of Environmental Management, 2026)

Non-directly bonded single-atom pairs towards H2/CO electrooxidation - Tongtong Yang; Heng Liu; Hengjie Liu; Weiyi Zhao; Jiawei Ge; Wenhui Wang; Shuai Yang; Meijian Tang; Kai Wei; Kangcheng Wang; Zeming Qi; Xian Wang; et al. (Science Bulletin, 2026)

Pathogen-induced H2O2 triggers phosphorylation of the RNA-binding protein RRM2R to suppress OsMAPKKK18 intron retention for orchestrating rice immunity and growth - Xiang Lu; Yibang An; Wenxiu Lu; Jing Li; Qing Xiong; Miaomiao Zhu; Yao He; Jia Yang; Yue Wang; Zeming Zhang; Xiaorong Gong; Yulong Qian; et al. (Molecular Plant, 2026)

A durable immuno-protective core-shell microgel for the enhanced pancreatic islet transplantation in diabetes therapy - Zeming Hu; Yang Luo; Muhammad Junaid; Rong Xu; Yaoqi Chen; Jie Yao; Renhao Ni; Tong Zhu; Hua Zhang; Huiqing Ding; Yabin Zhu (Chemical Engineering Journal, 2025)

Extremely high toxicity of gaseous intermediate/semi volatile organic compounds emitted from typical incomplete biomass burning in China - Yueqian Wang; Di Wu; Zihua Guo; Xiu Chen; Yang Li; Yifei Tan; Zeming Ye; Yuzhe Liu; Yaoqiang Huo; Qing Li; Jianmin Chen (Journal of Hazardous Materials, 2025)

Controlled-release oxidants for in situ remediation of organic contaminated soil and groundwater: Material preparation, mechanisms, and applications - Jia Shen; Zili Jiang; Hongyun Shao; Zeming Xie; Yue Han; Jia Liu; Hongxin Chen; Shijin Feng; Yang Liu; Xiuxiu Ruan (Journal of Hazardous Materials, 2025)

Critical control points in Penaeus vannamei aquaculture: Dynamic tracking and comprehensive risk assessment of antibiotics - Feng Xu; Chenxue Yang; Hua Liu; Hao Liu; Mingze Chen; Yinliang Wu; Xizhi Shi; Zeming Zhang; Rongrong Zhang (Journal of Hazardous Materials, 2025)

Identification of Mitochondrial and Succinylation Modification-Related Gene Signature in Ischemic Stroke - Lixia Wang; Jishuai Zhao; Hui Cai; Xiaoling Ying; Yonglei Liu; Zeming Luo; Heyan Chen; Lin Yang (Molecular Neurobiology, 2025)

A lightning augmented recurrent nowcasting model based on self-supervised learning and multi-modal fusion method - Liang Zhang; Qian Li; Zeming Zhou; Kangquan Yang (Atmospheric Research, 2025)

Co-exposure to enrofloxacin and atrazine enhances the hepatotoxicity in Larimichthys crocea by targeting the hypothalamic–pituitary–thyroid and gut–liver axes - Yinan Wang; Chenxue Yang; Qiangqiang Shi; Liuquan Zhang; Hao Liu; Jinjie You; Rongrong Zhang; Aili Sun; Suquan Song; Zeming Zhang; Xizhi Shi (Journal of Hazardous Materials, 2025)

Seasonal and spatial variations of nutrients and environmental effects under anthropogenic influence in Daya Bay, China - Jincheng Zhao; Jiawei He; Cai Li; Zeming Yang; Cong Liu; Xianqing Zhang; Min Qin; Dejing Tang; Wen Zhou; Zhantang Xu; Yuanyue Cheng (Frontiers in Marine Science, 2025)
Nutrients are crucial factors for the growth of phytoplankton, and their biogeochemical processes directly impact marine biodiversity. In this study, based on two cruise observations in spring and summer of 2024, the seasonal and spatial variations of nutrients, chlorophyll a, and other ecological indicators in Daya Bay were explored. The results indicated that the average concentrations of dissolved inorganic nitrogen and silicate were 3.61 ± 3.99 µM and 26.27 ± 13.91 µM in summer, respectively, compared with 2.48 ± 1.53 µM and 23.8 ± 6.77 µM in spring. The average concentration of dissolved inorganic phosphate was 0.29 ± 0.12 µM in summer, lower than 0.32 ± 0.09 µM in spring. The stoichiometric proportion among nutrients at most monitoring stations were far from Redfield ratio, and a succession from N-limited to P-limited was observed. A transformation has been observed in the dominant composition of dissolved inorganic nitrogen, shifting from ammonia to total oxidized nitrogen as the main component, which is mainly attributable to the decrease in aquaculture activities in Daya Bay over the last 3 years. In addition, the warm wastewater discharge from nuclear power stations directly influences the distribution of phytoplankton in the surrounding areas. This study provides timely information regarding recent shifts in ecological indicators and is significant to the ecological protection, environmental management, and policy adjustment in Daya Bay.

Single-cell atlas profiling revealed cellular characteristics and dynamic changes after PD-1 blockade therapy of brain metastases from laryngeal squamous cell carcinoma - Yunzhi Zou; Hao Duan; Zekun Deng; Rong Xiang; Jixiang Zhao; Zhenhua Zhang; Wanming Hu; Yuanzhong Yang; Zeming Yan; Shujuan Wen; Zexian Liu; Gao Zhang; et al. (Molecular and Cellular Biochemistry, 2025)
Brain metastasis (BM) in laryngeal squamous cell carcinoma (LSCC) is uncommon but prognosis is poor. Anti-PD-1 immunotherapy benefits some advanced LSCC cases, yet its efficiency is limited by tumor complexity. We analyzed paired metastatic tumor samples from before and after immunotherapy using single-cell RNA sequencing (scRNA-seq), along with a primary LSCC dataset and bulk RNA sequencing. This identified changes post-immunotherapy and revealed differences in single-cell transcriptomes among LSCC, primBM, and neoBM. Our findings show that anti-PD-1 treatment suppresses metastasis-promoting pathways like VEGF and EMT in cancer cells, and alters immune cell functions. Notably, it upregulates T cell activation, leading to CD8 T cell exhaustion from excess heat shock proteins, notably HSPA8. However, CD8 T cell cytotoxic functions improve post-treatment. In myeloid cells, anti-PD-1 therapy enhances antigen presentation and promotes a proinflammatory shift post-metastasis. Additionally, NUPR1 is linked to BM in LSCC, and NEAT1 is a potential metastatic cancer cell cycle participant. Our study provides insights into cancer heterogeneity and the impact of PD-1 immunotherapy on metastasis, aiding precise diagnosis and prognosis.

A microfluidic analyzer based on liquid waveguide capillary cells for the high-sensitivity determination of phosphate in seawater and its applications - Jincheng Zhao; Zeming Yang; Dejing Tang; Min Qin; Wen Zhou; Cong Liu; Zhantang Xu; Yuanyue Cheng; Xianqing Zhang; Cai Li (Analytica Chimica Acta, 2024)

Ions release stages of Cu-Pb-Zn mine tailings waste: A column leaching simulation - Lei Xu; Liang Tang; Zeming Shi; Jingsong Yang; Kunhao Shi; Haili Zhang; Yuting Yuan (Ore and Energy Resource Geology, 2024)

Exploring covariabilities of the high-summer subtropical upper-level pressure systems in the Northern Hemisphere - Ziyun Huang; Chundi Hu; Kaiqiang Deng; Zeming Wu; Chengyang Zhang; Tao Lian; Guoli Zhang; Lifei Lin; Song Yang (Atmospheric Research, 2024)

Synergistic benefits of Funneliformis mosseae and Bacillus paramycoides: Enhancing soil health and soybean tolerance to root rot disease - Zhichao Yang; Jie Kang; Zeming Ye; Wei Qiu; Jiaxin Liu; Xinbo Cao; Jingping Ge; Wenxiang Ping (Environmental Research, 2023)

Suppressing hydrogen evolution and eliminating sulfation in lead-carbon batteries via potential-matching g-C3N4@rGO nanosheets - Daiwen Tao; Xiong Liu; Simiao Huang; Zeming Li; Hui Yang; Jinyu Wang; Qilong Zhang (Chemical Engineering Journal, 2023)

Chain-mediating effect of interaction between telomeres and mitochondria under oxidative stress in coke oven workers - Zhiguang Gu; Zeming Niu; Zhaofan Yan; Yahui Fan; Jing Sun; Xiangkai Zhao; Xiaoran Duan; Wu Yao; Yongli Yang; Wei Wang (Environmental Pollution, 2023)

Lead single atoms anchored on reduced graphene oxide as multifunctional additive for lead–carbon battery - Daiwen Tao; Xiong Liu; Zeming Li; Hui Yang; Jinyu Wang; Qilong Zhang (Chemical Engineering Journal, 2023)

Ammonium Impacts on Vibrations of Hydroxyl and Lattice of Phengite at High Temperature and High Pressure - Weihua Huang; Yan Yang; Zeming Qi; Wendi Liu; Zhongping Wang; Yan Liu; Qunke Xia (Journal of Earth Science, 2021)

Urban trees in university campus: structure, function, and ecological values - Xueyan Wang; Yanlin Wang; Xiaohan Qu; Bing Huang; Zeming Li; Junjiao Sun; Xiaoqing Wei; Xiuying Yang (Environmental Science and Pollution Research, 2021)

Construction and application of a comprehensive coordination and cross-efficiency sustainable development evaluation model: a case study of 31 provinces and regions in China - Guowei Che; Zeming Wang; Zhengli Yang (Environment, Development and Sustainability, 2021)

Uranium sorption onto mullite: Characteristics of isotherms, kinetics and thermodynamics - Liao Rong; Shi Zeming; Hou Yun; Zhang Kailiang; Zhang Junji; Wang Xinyu; Cheng Ke; Yang Lvhang (Journal of Earth System Science, 2019)

Crystal structure of norsethite-type BaMn(CO3)2 and its pressure-induced transition investigated by Raman spectroscopy - Wen Liang; Lin Li; Yuan Yin; Rui Li; Zeming Li; Xiqiang Liu; Chaoshuai Zhao; Shuguang Yang; Yong Meng; Zengsheng Li; Yu He; Heping Li (Physics and Chemistry of Minerals, 2019)

Maternal doubled haploid production in interploidy hybridization between Brassica napus and Brassica allooctaploids - Shaohong Fu; Liqin Yin; Mingchao Xu; Yun Li; Maolin Wang; Jin Yang; Tingdong Fu; Jisheng Wang; Jinxiong Shen; Asif Ali; Qiong Zou; Bin Yi; et al. (Planta, 2018)

A modified GAC model for extracting waterline from remotely sensed imagery - Kun Ruan; Yong Zha; Zeming Zhou; Pinglv Yang (International Journal of Remote Sensing, 2016)

Detection of inherited mutations for hereditary cancer using target enrichment and next generation sequencing - Yanfang Guan; Hong Hu; Yin Peng; Yuhua Gong; Yuting Yi; Libin Shao; Tengfei Liu; Gairui Li; Rongjiao Wang; Pingping Dai; Yves-Jean Bignon; Zhe Xiao; et al. (Familial Cancer, 2015)

UHP metamorphic rocks from the Chinese continental scientific drilling project: I. Petrology and geochemistry of the main hole (0–2,050 m) - Zeming Zhang; Yilin Xiao; Zhiqin Xu; Jochen Hoefs; Jinsui Yang; Fulai Liu; J. G. Liou; Klaus Simon (Contributions to Mineralogy and Petrology, 2013)